Study of the relationship components affecting on the amount of social interactions in the compressed areas (Case Study: Aspeh Kola Neighborhood, Amol city) - farzin mahmodi pati; zohre bolori (نشریه جغرافیا و برنامه‌ریزی, 2019)
The growth of increasing citizenship aspects and the formation of the new values from the city growth during the recent years caused that the contemporary city and city making face to a novel challenging as the study of social domains have a great importance in recent years .The main case of this research is the study of the relationship components affecting on the amount of social interactions.The current research method is analytical -descriptive and it is applied in purpose. The statistical population studied is people who live in Aspeh Kola Amol with 1773 household which were selected among 375 families using the simple random sampling. The reliability of the main scale of the questionnaire calculated by 0.849 Cronbach's alpha. and the analysis of the data was done by Structural Equations for the scientific measuring, reliability surviving and accesing of the model. The outcoming result show that there are relationship among the components of framework structure, enviromental understanding and the amount of social interactions. in addition to the above relationships, it is confirmed that there are relationship between political culturl- social structure and the environmental framework structure with the amount of social interactions with interfacing of environmental understanding.